Composition Analysis of Vegetation in Sub-Sub DAS Khilau Kabupaten Pesawaran - Atikah Badzlina; Irwan Sukri Banuwa; Afif Bintoro; Duryat Duryat (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
The changes in land use often affect biodiversity. Eventually, it would affect the composition of the vegetation in the protected forest in KPHL Kabupaten Pesawaran, especially in Sub-sub-watershed Khilau. This study aimed to analyze the composition of the vegetation on the various classes of land cover in Sub-sub-watershed Khilau. The main location of the study was conducted in the CCCD site project area. The used method was vegetation analysis with checkered lines as a sampling method. The results of the vegetation analysis of the entire important species growth phase that were found with the largest number were 78 species from each land cover in the tree phase. The lowest number was 33 species in the sapling phase, not even in the seedling phase was found in each land cover. Rehabilitation is urgently needed to maintain functions in the protected areas of the Khilau watershed.